Evaluation of thermal performance of packaged GaN HEMT cascode power switch by transient thermal testing. (5th April 2016) - Chen, Szu-Hao; Chou, Po-Chien; Cheng, Stone
Highlights: This work proposes a simple and fast non-destructive thermal analysis method. The variations of on-resistance Ron with temperature are extracted and established. The experiments demonstrated the feasibility of in-situ thermal characterization. Abstract: In this investigation, thermal transient measurements and analyses are used to study the thermal performance of a cascoded GaN power device. The method is based on the thermal characterization of the on-resistance ( Ron ) of the device and the synchronized current–voltage characteristics under continuous operation. The changes in Ron with temperature (25 °C–180 °C) are measured, statistically studied, and correlations investigated. The proposed method for estimating transient thermal impedance has the following characteristics: (1) it is robust and reproducible; (2) it yields a heating curve to prevent over-heating for the device under test (DUT); (3) it provides in-situ current–voltage characterization; (4) it includes a transient offset correction for initial transient electrical disturbances (such as current collapse); (5) it optimizes a compact thermal model; (6) it is sensitive to package structure and design variables. This monitoring of thermal impedance variation provides a simple and fast non-destructive method for analyzing power switching devices during thermal testing. Satisfactory experimental results confirm the feasibility of in-situ current–voltage characterization and the real power varies with the thermal impedance.